Omega‐3 fatty acids predict recurrent venous thromboembolism or total mortality in elderly patients with acute venous thromboembolism. (January 2017) - Reiner, M. F.; Stivala, S.; Limacher, A.; Bonetti, N. R.; Méan, M.; Egloff, M.; Rodondi, N.; Aujesky, D.; von Schacky, C.; Lüscher, T. F.; Camici, G. G.; Beer, J. H.
Abstract : Essentials The role of omega‐3 fatty acids (n‐3 FAs) in recurrent venous thromboembolism (VTE) is unknown. Association of n‐3 FAs with recurrent VTE or total mortality was investigated in 826 patients. Whole blood n‐3 FAs were inversely correlated with recurrent VTE or total mortality. Major and non‐major bleeding was not increased in patients with higher levels of n‐3 FAs. Summary: Background: The role of omega‐3 fatty acids (n‐3 FAs) in recurrent venous thromboembolism (VTE) remains unknown. Objectives: To investigate the association of n‐3 FAs with recurrent VTE or total mortality at 6 months and 3 years. Methods: N‐3 FAs were assessed in 826 patients aged ≥ 65 years, categorized into low, medium and high based on the 25th and 75th percentile. Mean follow‐up was 29 months. Results: At 6 months, subjects with medium (adjusted hazard ratio [HR], 0.37; 95% confidence interval [CI], 0.22–0.62) and high n‐3 FA levels (adjusted HR, 0.36; 95% CI, 0.20–0.67) were less likely to develop recurrent VTE or total mortality, compared with those with low n‐3 FAs. At 3 years, medium levels (adjusted HR, 0.67; 95% CI, 0.47–0.96) were associated with lower risk of recurrent VTE or total mortality. As compared with low n‐3 FAs, the adjusted sub‐hazard ratio [SHR] of recurrent VTE was 0.39 (95% CI, 0.15–0.99) in patients with medium and 0.17 (95% CI, 0.03–0.82) in patients with high n‐3 FAs. The cumulative incidence of recurrent VTE was lower in the medium and high n‐3 FA groups as compared with the low n‐3 FA groups, but seems to have worn off after 3 years. The incidence of major and non‐major bleeding was not greater in the high n‐3 FA group. Conclusion: Higher levels of n‐3 FAs were associated with a lower risk of recurrent VTE or total mortality in elderly patients with VTE, but not with greater bleeding risk.